Integrative Medicine (Herbal Medicine Combined with Drug Therapy) for Behcet's Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ji Hee Jun; Lin Ang; Tae Young Choi; Hye Won Lee; Myeong Soo Lee (MDPI AG, 2021)
This review aimed to investigate the efficacy of integrative medicine (herbal medicine combined with drug therapy) in the treatment of Behcet's disease (BD). Eleven databases were searched from their inception to 7 December 2020, for randomized control trials (RCTs) that reported the effects of integrative medicine in treating BD. The risk of bias was assessed using seven domain criteria from the Cochrane Collaboration tool. Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to assess the quality of evidence. The direction of the effect is also shown in the form of an albatross plot. Sixteen trials met the inclusion criteria and were analyzed. The overall risk of bias was determined to be uncertain. The meta-analysis showed a superior response rate with herbal medicine plus drug therapy (relative risk (RR) 1.19, 95% confidence interval (CI) 1.13 to 1.25, n = 1034, p < 0.00001, I2 = 0%, low certainty of evidence (CoE)) compared to drug therapy. Integrative medicine also lowered the recurrence rate after 2 months of follow-up (RR 0.27, 95% CI 0.09 to 0.76, n = 120, p = 0.01, I2 = 0%, low CoE). The erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) level, and skin lesions were also significantly improved using integrative medicine, but equivalent effects were seen for oral ulcers, genital ulcers, and eye inflammation. Minor adverse events were reported in both groups. Our findings suggest that herbal medicine combined with drug therapy is more effective for the treatment of BD than drug therapy alone. Although the type of drug therapy used varied across the studies, integrative medicine was shown to improve the total response rate, skin lesions, the ESR, and the CRP level. However, the overall risk of bias of the studies was concerning, and the CoE was low. Information on adverse events (AEs) was also insufficient. In addition, the number of studies included for data synthesis for most outcomes was small. Future studies with rigorous RCTs may help establish the efficacy of integrative medicine in the treatment of BD.